Labor Market Effects of Bounds on Domestic Outsourcing - Bruno Jiménez; Silvio Rendon (Institute of Labor Economics (IZA), 2022)
We investigate the labor market effects of putting bounds to domestic outsourcing in Peru. A series of difference-in-differences specifications for individuals with high versus low predicted propensities to be outsourced show evidence of non-negative labor market effects. Limiting domestic outsourcing increases labor force participation by 1.5 percentage points and employment by 2.3 percentage points while it reduces unemployment by 0.8 percentage points, but has no statistically significant impact on labor formality nor real wages. Our results suggest that a policy of restricting outsourcing does neither destruct jobs nor does it improve workers' labor market conditions in the short-run.
Keywords: J21; J48; E24; 330; domestic outsourcing; employment